Influenza surveillance in Europe: establishing epidemic thresholds by the Moving Epidemic Method. Issue 4 (16th August 2012) - Vega, Tomás; Lozano, Jose Eugenio; Meerhoff, Tamara; Snacken, René; Mott, Joshua; Ortiz de Lejarazu, Raul; Nunes, Baltazar
<x xml:space="preserve">Abstract</x> Please cite this paper as: Vega et al. (2012) Influenza surveillance in Europe: establishing epidemic thresholds by the moving epidemic method. Influenza and Other Respiratory Viruses 7(4), 546–558. Background Timely influenza surveillance is important to monitor influenza epidemics. Objectives (i) To calculate the epidemic threshold for influenza‐like illness (ILI) and acute respiratory infections (ARI) in 19 countries, as well as the thresholds for different levels of intensity. (ii) To evaluate the performance of these thresholds. Methods The moving epidemic method (MEM) has been developed to determine the baseline influenza activity and an epidemic threshold. False alerts, detection lags and timeliness of the detection of epidemics were calculated. The performance was evaluated using a cross‐validation procedure. Results The overall sensitivity of the MEM threshold was 71·8% and the specificity was 95·5%. The median of the timeliness was 1 week (range: 0–4·5). Conclusions The method produced a robust and specific signal to detect influenza epidemics. The good balance between the sensitivity and specificity of the epidemic threshold to detect seasonal epidemics and avoid false alerts has advantages for public health purposes. This method may serve as standard to define the start of the annual influenza epidemic in countries in Europe.